2019
DOI: 10.1093/jnci/djz008
|View full text |Cite
|
Sign up to set email alerts
|

Trends in BRCA Test Utilization in an Integrated Health System, 2005–2015

Abstract: Background Genetic testing to determine BRCA status has been available for over two decades, but there are few population-based studies of test diffusion. We report 10-year trends in BRCAtesting in an integrated health-care system with long-standing access to genetic services. Methods A cohort of women aged 18 years and older was created to ascertain BRCA testing (n = 295 087). Annual testing rates between 2005 and 2015 were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 32 publications
1
30
0
Order By: Relevance
“…We did not ask about income (because of privacy issues) and it is possible that for some women, the lack of resources was an impediment to testing. Similar patterns of testing uptake have been seen in populations where testing is covered by insurance [ 22 ]. Although most tested individuals were white, all major ethnic groups were represented, including French-Canadians, East Asian, South Asian, indigenous, African and Hispanic among tested individuals.…”
Section: Discussionsupporting
confidence: 61%
“…We did not ask about income (because of privacy issues) and it is possible that for some women, the lack of resources was an impediment to testing. Similar patterns of testing uptake have been seen in populations where testing is covered by insurance [ 22 ]. Although most tested individuals were white, all major ethnic groups were represented, including French-Canadians, East Asian, South Asian, indigenous, African and Hispanic among tested individuals.…”
Section: Discussionsupporting
confidence: 61%
“…Refusal of testing can be at least in part attributed to the lack of insurance coverage. However, Knerr et al [31] reported an underutilization of BRCA1/2 testing even in an integrated health system offering adequate coverage of genetic services. The question as to whether psychological reasons could be at work in explaining this phenomenon remains open and warrants further scrutiny.…”
Section: Discussionmentioning
confidence: 99%
“…Healthcare professionals (surgical oncologists, medical oncologists, and specialized nurses) should identify patients at risk of carrying a variant in a breast cancer gene (e.g., BRCA1, BRCA2, CHEK2, PALB2, ATM genes), inform them about genetic testing, refer them for genetic counseling, or request a test themselves. Yet, despite the fact that genetic testing has been available for over two decades, many eligible women do not receive BRCA testing (Knerr et al 2019) and for certain groups of patients, the substantial underutilization of genetic testing is even larger (Cohen et al 2019). Previous research has shown that there is unequal access to cancer genetic testing for patients with lower educational levels and those with a migrant background (van Riel et al 2012;Kurian et al 2017;Delikurt et al 2015;McCarthy et al 2016;van der Giessen et al 2017).…”
Section: Introductionmentioning
confidence: 99%